Short-term recovery of physical activity and knee function after an acute knee injury - Sanne Fomin; Håkan Gauffin; Joanna Kvist (BMJ Open Sport & Exercise Medicine, 2020)
Objectives To describe self-reported knee function, participation in physical activity and the number of knee surgeries at 3 and 6 months following acute knee injury.Methods Prospective cohort study. Participants, aged 15–40 years with an acute knee injury sustained no more than 6 weeks prior to inclusion, were recruited. There were 279 participants with ACL injury and 101 participants with other acute knee injuries included. Follow-up questionnaires were sent at 3 and 6 months after injury. Demographic information, activity participation, International Knee Documentation Committee subjective knee form (IKDC-SKF) and the Single Assessment Numeric Evaluation (SANE) score were collected. Additional knee injuries were obtained from self-report and medical charts.Results The IKDC-SKF, SANE and physical activity participation were reduced at 3-month and 6-month follow-up. The number of participants who achieved health-promoting physical activity levels was reduced by 50% at 6-month follow-up compared with before injury. Seventeen per cent of participants with ACL injury and 41% of participants with other acute knee injuries had returned to their preinjury physical activity at 6 months. Participants with ACL injury reported worse knee function, lower physical activity participation and had more surgeries (128 surgeries, including 109 ACL-reconstructions) compared with participants with other acute knee injuries (six surgeries).Conclusion Acute knee injuries, including ACL injuries, affected self-reported knee function and physical activity participation for at least 6 months after index injury. More research is needed to understand how best to help people with acute knee injuries return to physical activity and achieve satisfactory knee function.